AB0113 ANTIBODIES AGAINST HELICOBACTER PYLORI ANTIGENS IN PATIENTS WITH PSORIATIC ARTHRITIS AND PSORIASIS. (13th June 2020) - Patrikiou, E.; Efthymiou, G.; Liaskos, C.; Ntavari, N.; Zfiriou, E.; Simopoulou, T.; Scheper, T.; Meyer, W.; Roussaki-Schulze, A.; Bogdanos, D.
Abstract : Background: Psoriasis (Ps) and Psoriatic Arthritis (PsA) are inflammatory diseases of unknown etiology. Helicobacter pylori (Hp) infection has been hypothesized as one of the microbial agents that can lead to development of immune-mediated psoriatic disease, but the nature of the specific Hp antigens involved remains unclear. Objectives: To asses antigen specific antibody responses against immunodominant Hp antigens in patients with psoriatic diseases. Methods: Ninety-one patients with Ps (35 females; median age 51.9, age range 25-87), 47 patients with PsA (25 females; median age 52.9, age range 25-87) and 60 demographically matched healthy controls (HC) were studied. Reactivity to Hp-specific antigens were tested by Western immunoblotting (in combination with line immunoassay for anti-CagA and anti-VagA antibody testing) (Euroimmun AG, Lübeck, Germany). Results: Positivity against Hp was comparable between PsA (38.3%), Ps (39.6%) and HCs (50%). Anti-p66-UreB, anti-p54-flagelin and anti-p29-UreA abs were more frequent in psoriatic patients compered to healthy controls (p66: 94.4% in Ps vs 69.7% in HC, p=0.017; p54: 66.7% in Ps vs 33.3% in HC, p=0.012; p29 72.2% in Ps vs 45.5% in HC, p=0.044) and anti-p29-UreA abs were detected in higher frequency in PsA patients compered to HC (94.4% vs 45.5%, p=0.002). Reactivities against the remaining Hp antigens were comparable between Ps and PsA patients and HC. Conclusion: Antibody responses against p66-UreB, p29-UreA, and p54-flagelin are more prevalent in patients with psoriatic disease, suggesting their potential involvement in PsA and Ps. Disclosure of Interests: Eleni Patrikiou: None declared, George Efthymiou: None declared, Christos Liaskos: None declared, Niki Ntavari: None declared, Efterpi Zfiriou: None declared, Theodora Simopoulou: None declared, Thomas Scheper, Employee of: Employee of EUROIMMUN AG, Lubeck, Germany, Wolfgang Meyer Employee of: Employee of EUROIMMUN AG, Lubeck, Germany, Aggeliki Roussaki-Schulze: None declared, Dimitrios Bogdanos: None declared